Continuous flow system for simple preparation of functionalized polymeric beads from poly(acrylamide-thiolactone). Issue 34 (18th August 2022) - Valverde, David; Porcar, Raúl; Prinzi, Roberta; Luis, Santiago V.; Altava, Belén; García-Verdugo, Eduardo
Abstract : Going with the flow: continuous flow devices to fabricate functional spherical polymers based on poly(acrylamide-thiolactone). Abstract : Here we report on a simple and robust approach based on continuous flow devices to fabricate functional spherical polymers in 6 minutes. The presence of thiolactone groups allows the introduction of two functionalization levels. Soluble poly(acrylamide-thiolactone) is converted in the presence of an amine and a crosslinker in the corresponding spheres via continuous droplet generation and an in situ gelation and cross-linking process. The key experimental variables for the preparation of functional spherical polymers were evaluated and optimised. The functionalized beads were modified and preliminarily tested in catalytic applications.